LABORATORY APPLICATION DESIGN - Pajar Machmud; Halida Indriati; Herianto Saputra; Abdul Halim (Yayasan Putra Adi Dharma, 2024)
Employee payroll applications are designed with the aim of minimizing errors caused by human error, closing time in data collection and management of employee salaries, research methods used namely by library study techniques, retrieving information from the internet, and also by conducting field studies to related institutions. obtained from the design of employee employee applications to produce results that are quite effective compared to the employee payroll system manually, applications are made using Microsoft Visual Basic as a software to create a database.